Bisphosphonate-based molecules as potential new antiparasitic drugs - Branco Santos, Joice Castelo (2021)
Neglected tropical diseases such as Chagas disease and leishmaniasis affect millions of people around the world. Both diseases affect various parts of the globe and drugs traditionally used in therapy against these diseases have limitations, especially with regard to low efficacy and high toxicity. In this context, the class of bisphosphonate-based compounds has made significant advances regarding the chemical synthesis process as well as the pharmacological properties attributed to these compounds. Among this spectrum of pharmacological activity, bisphosphonate compounds with antiparasitic activity stand out, especially in the treatment of Chagas disease and leishmaniasis caused by Trypanosoma cruzi and Leishmania spp., respectively. Some bisphosphonate compounds can inhibit the mevalonate pathway, an essential metabolic pathway, by interfering with the synthesis of ergosterol, a sterol responsible for the growth and viability of these parasites. Therefore, this review aims to present the information about the importance of these compounds as antiparasitic agents and as potential new drugs to treat Chagas disease and leishmaniasis.